Extended life settings and protection of metal from corrosion and of products эffektyvnыm эkolohychesko chystыm funds rastitelno origin - Savenko, V.; Vysotska, L.; Sheinich, L.; Klyuyeva, V.; Nazarenko, M. (Ways to Improve Construction Efficiency, 2015)
Corrosion leads to billions of losses each year, consisting in putting down articles and machines made of metal, as well as the costs for the protection and restoration of metal products. Investigation of corrosion provides a basis to assert that the corrosion protection - is primarily a correct surface preparation and then a layer of high-quality sealants, paints or other types of coverage. Environmentally friendly plant substance, patented and tested, with the name "CONTRRUST" is an effective means of blocking sources of corrosion (rust) and surface preparation for protective coatings.